Industrial Training Report: Sultan Abdul Samad Library / Mohamad Zulfahmi Abdul Halim - Abdul Halim, Mohamad Zulfahmi (Universiti Teknologi MARA, Negeri Sembilan, 2020)
That most of the institution or university that is required to pursue Industrial training applies to real work experience that is important to career development before the next steps to graduation during the study programme. It administers pre-professional work experience with specific task and responsibilities. Student is supposed to contribute to the activities of the workplace and meet the same demands of work production and responsibility expected by the organization of its regular employees. This report made to fulfil requirement of the Industrial Training subject IMC690 for final year students Faculty of Information Management in Bachelor of Science Information (Hons.) Library Management. This purpose of this report is to explain in detail about tasks and lesson learnt along the five (5) months industrial training at Perpustakaan Sultan Abdul Samad (PSAS). Starts from briefing about background and organizational structure in Chapter 1, it will give thorough imagination to readers on organization information in the next chapter. Besides that, tasks and responsibilities given during the practical training will be highlighted on training activities and special project handled by the trainee. Last but not least, last chapter will be discuss about industrial training reflection especially on trainee's application of knowledge, personal thoughts, lesson learnt during industrial training. Other than that, organizational weaknesses will be recognized and any advice would propose improving the organization's management and core business.